Hypercholesterolaemia is not associated with early atherosclerotic lesions in primary biliary cirrhosis. Issue 12 (21st April 2006) - Allocca, M; Crosignani, A; Gritti, A; Ghilardi, G; Gobatti, D; Caruso, D; Zuin, M; Podda, M; Battezzati, P M
Abstract : Background: Hypercholesterolaemia often occurs in primary biliary cirrhosis (PBC) as a result of chronic cholestasis, but whether these patients are exposed to greater cardiovascular risk is unknown. Aim: To establish whether hypercholesterolaemia is associated with subclinical atherosclerosis in PBC. Patients: 103 consecutive patients with PBC (37 with total cholesterol ⩾6.21 mmol/l) and 37 controls with hypercholesterolaemia, and 141 matched controls with normocholesterolaemia. Methods: Ultrasound imaging of carotid artery to determine intima–media thickness (IMT) and stenosis. Results: Controls with hypercholesterolaemia had higher IMT and prevalence of carotid stenosis compared with patients with hypercholesterolaemic PBC (mean (SD) 0.850 (0.292) mm v 0.616 (0.137) mm, pc <0.001; 43% v 19%, pc = 0.129) who, in turn, were similar to the 66 patients with normocholesterolaemic PBC (0.600 (0.136) mm; 5%). Compared with subjects with normocholesterolaemia, controls with hypercholesterolaemia, but not patients with hypercholesterolaemic PBC, had an increased risk of raised IMT (odds ratio (OR) 5.4, 95% confidence interval (CI) 2.5 to 11.9, p<0.001; and 0.7, 0.3 to 2.0, p = 0.543) or carotid stenosis (8.2, 3.4 to 20, p<0.001; and 2.5, 0.9 to 6.9, p = 0.075). In PBC, compared with younger patients without hypertension, the risk of increased IMT was OR (CI) 3.1 (0.6 to 17; p = 0.192) in patients with hypertension or old age, but not hypercholesterolaemia, and 4.6 (0.8 to 27; p = 0.096) in patients who also had hypercholesterolaemia. The corresponding figures for risk of stenosis were 3.6 (0.4 to 36; p = 0.277) and 15.8 (1.8 to 141; p = 0.014). Conclusions: Hypercholesterolaemia is not consistently associated with subclinical atherosclerosis in PBC, but should be treated if other risk factors for cardiovascular disease are also present. The search for factors that may protect patients with hypercholesterolaemic PBC against atherosclerosis should be encouraged.